Ecotourism success story in Zimbabwe: The case of Tsholotsho CAMPFIRE project - Oliver Chikuta; Mark Russell; Felicity Ncube (MSU Press, 2023)
This study exposes the untold success story of Zimbabwe's ecotourism projects. Literature is awash with publications on the failure by Zimbabwe to come up with, and run sustainable ecotourism projects that significantly benefit the community with very little or no effort being put on telling the positive side of the ecotourism story. It is against this background that the researchers, using an exploratory design, investigated the story of the Ngamo CAMPFIRE project in Tsholotsho to establish the nature, and extent of its contribution to the environmental, socio-cultural and economic well-being of the local community. A qualitative research methodology was adopted which involved interviews with key informants (headman, Rural District Council [RDC] representative, headmaster), and panel discussions with local residents. The study revealed that indeed tourism has significantly impacted on the livelihoods of people in Tsholotsho especially in the Ngamo settlements which share a boundary with Hwange National Park. The key benefits include the construction of schools, employment, and training of local guides, scholarship programs, to mention just a few. The researchers recommended that other CAMPFIRE projects take a leaf from this project.